A Review of Coffee Kombucha Brewing and Health Effects as a Fermented Beverage - Sasongko, Devi Purnamasari (Jurnal Kebidanan dan Kesehatan Tradisional, 2025)
Background: Coffee kombucha, or what many kombucha brewers call koffucha, is one of the new varieties of kombucha, by replacing the tea infusion with coffee extract. However, the method of making koffucha still varies, like the coffee varieties, coffee extraction method, SCOBY and starter ratio, sugar ratio, fermentation time, and second fermentation. This review aims to examine koffucha brewing methods and its potential health benefits. Methods: This study reviewed the study about koffucha from previous literature using PRISMA method. The literature was gathered through a systematic search of PubMed, Scopus, and Google Scholar databases. Search terms included "coffee" and "kombucha," combined using Boolean operators. Results: The optimum method for koffucha brewing is 12 days of fermentation at room temperature 25˚C with a 10% sugar ratio. Robusta is considered better at total phenolic content, antioxidant level, and low sugar koffucha. Those who prefer low caffeine could opt for arabica with a lighter roasting level instead. The starter ratio and coffee ratio still vary and could not be concluded. Conclusion: The fermentation of coffee might increase its health properties, including antimicrobial, antifungal, anti-aging, and anti-neurodegenerative. In vivo study showed no sign of toxicity of koffucha. Koffucha shows potential as a functional beverage, but standardized methods and further validation are needed.